Analysis of Risk Factor and Mortality Among Acute Coronary Syndrome Patient: A Retrospective Cohort Study - Laksono, Bayu Budi (Babali Nursing Research, 2025)
Background: Acute coronary syndrome is the leading cause of death worldwide related to degenerative lifestyle-associated processes. The factors contributing to these cases are interconnected. Understanding these factors is essential for improving patient outcomes and tailoring treatment strategies.  This study aimed to explore demographic risk factors, medical history, and cardiopulmonary conditions that may contribute to mortality among acute coronary syndrome patients. Method: This study is a Survey/Observational study with a retrospective Cohort approach. The population of this study was all medical record data of patients with Acute Coronary Syndrome (ACS) who were treated at Lavalete Hospital – Malang from January to December 2023, with 76 patients' medical records in total.  The total sampling technique was obtained in this study, then analysed by STATA 17 at the (α<0.05) significant level. Result: It found that education level was a significant factor affecting mortality, with less educated individuals having a higher risk of death (P < 0.01). Meanwhile, demographic factors such as age, gender, and marital status showed no significant correlation with mortality. Conditions such as acute pulmonary oedema (P=0.02) and pneumonia (P=0.00) proved to be significant risk factors for mortality. In contrast, other conditions, such as cardiomegaly, pulmonary congestion, pleural effusion, and atherosclerosis, had no significant impact. Conclusion:  This study highlights acute pulmonary oedema and pneumonia as significant risk factors for mortality. Future studies should aim to include larger sample sizes and consider longitudinal data to better understand the complex relationships between medical history and mortality.